UNCERTAINTY ON THE BANKRUPT PROCESS AS A LEGAL MEANS FOR SHARIA ECONOMIC DISPUTE SETTLEMENT (Case Study of BMT Fisabilillah) - Rejeki, Niniek Mumpuni Sri (Jurnal Hukum dan Peradilan, 2022)
Law No. 1 of 2013 on Microfinance Institutions (MFIs) has provided a legal basis for the operational activities of MFIs. The development ofÂ  Sharia Microfinance Institutions/Baitul Maal wat Tamwil must be followed up with dispute resolution based on sharia principles. The intersection that occurs in the settlement of sharia economic disputes in bankruptcy cases is the mixing of conventional and sharia legal principles, which will cause legal uncertainty, the Court has absolute authority to handle sharia economic law cases. The bankruptcy decision by the Semarang Commercial Court in the BMT Fisabilillah case proves that at the empirical level, sharia economic disputes are decided by the Commercial Court which is formed in the general court environment. This article will analyze the position of BMT after the issuance of the MFI Law, the fall of the bankruptcy decision on BMT Fisabilillah. The research method is normative law by reviewing legal materials related to MFIs, Cooperatives, Bankruptcy and PKPU. The legal vacuum in bankruptcy law for sharia actors should be followed up by complying with the laws and decisions of the Constitutional Court so that bankruptcy disputes for LKMS become the domain of the Religious Courts, this is the main difference between bankruptcy based on positive law in Indonesia and Islamic law. This review of the bankruptcy case of BMT Fisabilillah is to understand that there is a blending in the substance of sharia economic law in the realm of general justice. This situation weakens the absolute authority of the established Religious Courts.